IMPLEMENTASI PEMBELAJARAN E-LEARNING MADRASAH DALAM MOTIVASI BELAJAR SISWA MATA PELAJARAN FIQIH KELAS VIIIMTS TARBIYAH ISLAMIAH HINAI KIRI - Hazijah Hazijah; Nurmisdaramayani Nurmisdaramayani; Usmaidar Usmaidar (Jurnal Iqtirahaat, 2023)
The background is that during Covid 19 learning was done online or distance learning (PJJ) made students less motivated in learning, therefore, Madrasah E-Learning based learning was applied. The objectives of this research were: To find out how the implementation of Madrasah E-Learning learning in the learning motivation of students in the Fiqh subject class VIII MTs Tarbiyah Islamiah Hinai Kiri. This research is an experimental type of research with a quantitative approach. However, there is no denying the existence of a qualitative approach to knowing and analyzing data on teacher abilities in implementing Madrasah E-Learning-based learning. The results showed that the application of Madrasah E-Learning in learning Fiqh could increase the learning motivation of class VIII MTs Tarbiyah Islamiyah Hinai Kiri, from the beginning of the pre-action to the end of cycle II. The results of the initial questionnaire on student learning motivation reached a percentage of 58%, and at the end of cycle I, the results of the questionnaire on student learning motivation reached a percentage of 68% and at the end of cycle II the results of the questionnaire reached 75%.